Echocardiography in the Evaluation of the Right Heart - Angelos Tsipis; Evdokia Petropoulou (US Cardiology Review)
The significance of the right ventricle (RV) as a predictor of outcome in a series of cardiac conditions has recently been recognized. Consequently, more studies are now focusing on improving the assessment of the RV. Its primary function is to support adequate pulmonary perfusion pressure in different circulatory and loading situations and to ensure that there is a low systemic venous pressure. Echocardiography is the first-line method of choice due to its accuracy when assessing RV structure and function, as well as its wide availability. The geometry of the RV is complex and its evaluation can be difficult. Integrating and combining multiple parameters may be a more reliable way to determine normal or abnormal function. Novel techniques are increasingly being performed more routinely in clinical practice and are facilitating diagnosis and treatment choices.